Using a co-design approach to develop aquatic reactive balance training for fall prevention - Anna Ogonowska-Slodownik; Julia O. Faria; Shanuga Thavarajah; Karina Pacholczyk; Birgit Blain; Myra Wiener; Jane Walker; Avril Mansfield; Soo Chan Carusone (PLoS ONE, 2026)
Background Falls are a major health concern among older adults, leading to injury, reduced independence, and increased healthcare cost. Reactive balance training can reduce fall risk, but barriers such as fear, joint discomfort, and harness burden limit its use – barriers that training in aquatic environment  may help overcome. Objective To design an aquatic reactive balance training (AquaReBal) program for older adults, integrating end-user perspectives to enhance safety, accessibility, and engagement. Methods Using a participatory design approach grounded in Participatory Action Research principles, we engaged three older adult partners, physiotherapists, and researchers in iterative phases including literature review, stakeholder consultations, practical pool sessions, and feedback meetings. Data collected through online meetings, surveys, field notes, and observations were reviewed using an inductive qualitative content analysis approach to inform iterative refinement of the intervention, following the Guidance for Reporting Involvement of Patients and the Public 2 framework. Results Three older adult partners and a multidisciplinary team co-designed the AquaReBal protocol through two participatory design sessions, one practical pool session, and two internal team sessions. Key recommendations from partners included using a vest instead of a hip belt for perturbations, addressing pool depth visibility, and creating an introductory package with practical information for participants. Partners emphasized safety, instructor support, and social engagement as critical for adherence and satisfaction. Conclusion The co-design process enabled the development of an AquaReBal protocol tailored to older adults’ needs and preferences, providing initial insights relevant to future feasibility and implementation.